On cubic equations over p-adic fields - Mukhamedov, Farrukh; Omirov, Bakhrom; Saburov, Mansoor (World Scientific, 2014)
We provide a solvability criterion for a cubic equation in domains . We show that, in principal, the Cardano method is not always applicable for such equations. Moreover, the numbers of solutions of the cubic equation in domains are provided. Since